Zeolite-silver-zinc nanoparticles: Biocompatibility and their effect on the compressive strength of mineral trioxide aggregate - Samiei, Mohammad (J Clin Exp Dent, 2017)
BACKGROUND: This study was carried out to evaluate the biocompatibility of zeolite-silver-zinc (Ze-Ag-Zn) nanoparticles and their effect on the compressive strength of Mineral Trioxide Aggregate (MTA). MATERIAL AND METHODS: Biocompatibility was evaluated by an MTT assay on the pulmonary adenocarcinoma cells with 0.05, 0.1, 0.25, 0.5, 1 and 5 mg/mL concentrations of Ze-Ag-Zn. For compressive strength test, four groups containing 15 stainless-steel cylinders with an internal diameter of 4 and a height of 6 mm were prepared and MTA (groups 1 and 2) or MTA + 2% Ze-Ag-Zn (groups 3 and 4) were placed in the cylinders. The compressive strength was evaluated using a universal testing machine 4 days after mixing in groups 1 and 3, and 21 days after mixing in groups 2 and 4. RESULTS: There was no significant difference between cytotoxicity of different concentrations. The highest (52.22±18.92 MPa) and lowest (19.57±5.76 MPa) compressive strength were observed in MTA group after 21 days and in MTA + 2% Ze-Ag-Zn group after four days, respectively. The effect of time and 2% Ze-Ag-Zn on the compressive strength were significant (P<0.05). Mixing MTA with Ze-Ag-Zn significantly reduced and passage of time from day four to 21 significantly increased the compressive strength. CONCLUSIONS: Mixing MTA with 2% Ze-Ag-Zn had an adverse effect on the compressive strength of MTA, but this combination had no cytotoxic effects. Key words:Compressive strength, Cytotoxicity, Mineral Trioxide Aggregate, Nanoparticle, Zeolite-Silver-Zinc.